Analysis of a Potential Halal Ecotourism on the Economic Awakening of Local Communities (Case Study in Brandan Barat District, Langkat Regency) - Nasution, Yenni Samri Juliati; Yafiz, Muhammad; Habibi, Adnan; Ritonga, Mirwansyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research describe an economic revival of the local community through the halal ecotourism program. The method used in this research is quantitative, this research is descriptive research. Descriptive is a way in which researchers condition an event based on values in the form of numbers and appear as they are, characteristics and relationships systematically, between phenomena to be studied at the research location. The results show that the background for the emergence of ecotourism programs is to see the natural potential that can be used as tourism based on environmental conservation efforts through cultural values, Ecotourism provides changes to the economic improvement of local communities. The stages of ecotourism development start from identification of empowerment to take advantage of natural potential accompanied by increasing community welfare based on faith values.